Pengaruh Firm Performance Terhadap Intellectual Capital Disclosure - Tang, Sukiantono; Angeline, Angeline (E-Jurnal Akuntansi, 2022)
Intellectual capital is an intangible asset consisting of human resources (human capital), corporate organization (structural capital), and relational value (relational capital) that can increase the value of a company. The research objective is to obtain empirical facts about the effect of firm size, minority share, liquidity, profitability, leverage, asset turnover, and market to book value on intellectual capital disclosure. The research was conducted on companies listed on the Indonesia Stock Exchange in 2017-2021. The selected sample results contained 1,827 observational data. The information analysis procedure used is linear regression analysis. The results of the research prove that firm size has a positive effect on intellectual capital disclosure. Minority share, liquidity, profitability, leverage, asset turnover, and market to book value do not affect intellectual capital disclosure. Keywords: Intellectual Capital Disclosure; Firm Performance.